Lumbar Spine Surgery Outcome :Effect of Regional Anaesthesia (Global Journal of Medical Research, 2015)
Either general or regional anesthesia can be used for spine surgery. Spine surgery involves acomplex procedure. The aim of a spine surgeon for doing a good surgery requires a clear and bloodless field especially in procedures done under microscope. As the working space is less a small epidural bleed can cause further complications in surgery. Another aspect is to take care of post operative analgesia which is better achieved with regional anaesthesia. Regional anaesthesiahas many benefits, namely less time, lower incidence of nausea and vomiting ,general hazards of general anaesthesia can be avoided and cost effectiveness. This article reviews effect of regional anaesthesia on lumbar spine surgery.
Keywords: anesthesia; general; spinal; lumbar surgery